Recovery optimization of an oil reservoir by water flooding under different scenarios; a simulation approach - Ayoub, M.A. (Maxwell Science Publications, 2015)
Water flooding used in secondary oil recovery to level up reservoir pressure can be enhanced in order to fit the reservoir conditions to optimally recover oil. The main goal consists in maximizing oil recovery while minimizing water production. As the dynamic of two immiscible flows is governed by its flow and rock properties and reservoir condition, the water flood optimization must be appropriately performed for a single reservoir. In this case study, it is shown theoretically and by means of Eclipse 100 that according to the basic elementary reservoir characteristics, certain parameters can be added and changed to obtain an optimum oil recovery for a faster and a slower water case. In each run reservoir characteristics and oil properties were fixed while water flooding parameters were changed. Both homogeneous and heterogeneous reservoirs were tested. Then, the graphs generated at each run are interpreted and the variables are adjusted accordingly. Much care was taken to minimize the cost while achieving high oil cut versus water cut (or water production) for the longest time interval within water flood life if not the whole duration. A single major problem which Eclipse 100 does not take into account is starting injection at an optimum time. As a result, both injection and production were started at the same time. Despite this, the cases were able to be compared with each other as with the initial base case (no injection). Moreover, conclusion and recommendations were drawn based on the results and analysis with regard to the recovery optimization. Â© Maxwell Scientific Organization, 2015.